2012
DOI: 10.1111/j.1365-2702.2012.04074.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of parental self‐efficacy experiences: maximising potential through health visiting and universal parenting support

Abstract: To maximise potential through parenting support, attention should be given to addressing factors associated with poorer self-efficacy experiences, including parental tiredness. Equally, practice should be directed at developing community environments that offer exposure to positive praise and the opportunity to practice new skills without facing criticism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 50 publications
0
23
0
1
Order By: Relevance
“…). Different forms of parenting support available can be identified by the mode of delivery and setting, with formal and informal help available for individuals, groups and families either in the home, community centres, specialist facilities or via virtual spaces supported by electronic media (Whittaker & Cowley ). Centre‐based support is often used as a key means of providing services for families with the most acute needs (Warren‐Adamson , Fernandez ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…). Different forms of parenting support available can be identified by the mode of delivery and setting, with formal and informal help available for individuals, groups and families either in the home, community centres, specialist facilities or via virtual spaces supported by electronic media (Whittaker & Cowley ). Centre‐based support is often used as a key means of providing services for families with the most acute needs (Warren‐Adamson , Fernandez ).…”
Section: Introductionmentioning
confidence: 99%
“…, Platt , Whittaker & Cowley ). One point concerns gender imbalances, with mothers being the predominant users of parenting services (Garrett , Whittaker & Cowley ). This arguably limits the extent that issues shared by mothers and fathers can be comprehensively addressed.…”
Section: Introductionmentioning
confidence: 99%
“…home visiting (de la Cuesta, 1994) A C C E P T E D M A N U S C R I P T o parenting programmes (Bateson et al, 2008;Whittaker and Cowley, 2012); o sleep behaviour clinics (Merrifield, 2005); o how to identify early indicators of childhood obesity and how to act on these to childhood obesity (Barlow et al, 2010) o how to supporting families where there may be issues of substance use (Orford et al, 2007); o how to intervene to promote infant mental health and to prevent behaviour problems (Craig and Power, 2010).  Skills in assessing and identifying family strengths as well as difficulties (Barlow, 2010)  Finely tuned listening skills to 'unlock issues' (especially for women with PND) and assist the person's sense of being able to manage their own condition (Turner et al, 2010)  Skilled focusing on the psychological well-being of the mother in PND (Morrell et al, 2009;  Ability to convey respect for the individual and understanding of their unique situation (Morrell et al,2011)  Active listening, conveying acceptance of the mothers' viewpoint (Morrell et al, 2011)  Helping the mother re-formulate her interpretation of life events and motivating healthy change (Morrell et al, 2011)  Listening skills : engagement, active listening, questioning, challenging (Barlow et al, 2010)  Skills in giving sensitive messages in a way which is meaningful and not threatening for the family and which maximises their likelihood of being acted upon (Barlow et al, 2010) Universal Plus: Abilities  The ability to work with families to set small goals which reflect family relationships and family dynamics …”
mentioning
confidence: 99%
“…The data supported this hypothesis and it appears to be an extension of prior research on childbirth trauma, as well as research into low parenting self-efficacy. Whittaker and Cowley (2012) reported that "lower self-efficacy scores correlated with high ratings for 'feeling tired' and 'receiving negative comments,'" both of which are themes reported in other studies concerning both parenting self-efficacy and childbirth-related posttraumatic stress (Coleman & Karraker, 2000;Creedy, et al, 2000).…”
Section: Childbirth-related Trauma and Parenting Self-efficacymentioning
confidence: 67%
“…Clinically, there are several points in which providers may be able to intervene, based upon the results of several recent studies (Alder et al 2008;Anderson, Melvaer, Videbech, Lamont, and Joergensen, 2012;Ayers et al, 2008;Ayers et al, 2006;Ayers et al, 2004;Ayers, and Warren, 2011;Harvey et al, 2003;Meades, Pond, Perez-Blasco, Rowan et al, 2007;Verreault et al, 2012;Viguer, and Rodrigo, 2013;and Whittaker and Cowley, 2012). I have synthesized the relevant findings in Figure 3.…”
Section: Clinical Implications and Direction For Future Researchmentioning
confidence: 99%